2013
DOI: 10.1186/1477-7525-11-100
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Malay version of sleep apnea quality of life index – preliminary results

Abstract: BackgroundThe objective of this study was to determine the validity and reliability of the Malay translated Sleep Apnea Quality of Life Index (SAQLI) in patients with obstructive sleep apnea (OSA).MethodsIn this cross sectional study, the Malay version of SAQLI was administered to 82 OSA patients seen at the OSA Clinic, Hospital Universiti Sains Malaysia prior to their treatment. Additionally, the patients were asked to complete the Malay version of Medical Outcomes Study Short Form (SF-36). Twenty-three patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Findings from these three studies showed that patients with CLE score significantly lower on both the physical component score (mean ± SD score 41 ± 13] and the mental component score (mean ± SD score 39 ± 12) compared with the general U.S. population (mean ± SD score 50 ± 10) . The psychometric properties of the SF‐36 were not evaluated in patients with CLE, even although the instrument has demonstrated evidence of acceptable reliability (internal consistency), construct validity (convergent and known groups) and ability to detect change (responsiveness and sensitivity to change) in other dermatological diseases, as well as other disease states …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from these three studies showed that patients with CLE score significantly lower on both the physical component score (mean ± SD score 41 ± 13] and the mental component score (mean ± SD score 39 ± 12) compared with the general U.S. population (mean ± SD score 50 ± 10) . The psychometric properties of the SF‐36 were not evaluated in patients with CLE, even although the instrument has demonstrated evidence of acceptable reliability (internal consistency), construct validity (convergent and known groups) and ability to detect change (responsiveness and sensitivity to change) in other dermatological diseases, as well as other disease states …”
Section: Resultsmentioning
confidence: 99%
“…3,6 The psychometric properties of the SF-36 were not evaluated in patients with CLE, even although the instrument has demonstrated evidence of acceptable reliability (internal consistency), construct validity (convergent and known groups) and ability to detect change (responsiveness and sensitivity to change) in other dermatological diseases, as well as other disease states. [57][58][59][60][61][62][63][64][65][66] Visual Analogue Scale VAS is an instrument used to measure a characteristic or attitude that is believed to range across a continuum of values and cannot easily be measured directly. 67 The VAS was devised to capture this idea of an underlying continuum.…”
Section: Short Form-36mentioning
confidence: 99%
“…Daily activities. Within the component of daytime functioning or daytime symptoms is the greatest number of coincidences within the scales developed to measure health-related quality of life in patients with OSAHS (9). The hypersomnia generated by the disease has an important impact on patients' lives.…”
Section: Quality Of Life Measurement Scales With the Syndromementioning
confidence: 99%
“…All this deteriorates the quality of life of patients who have the syndrome (4,5). The prevalence of this syndrome has increased in recent years (6,7,8,9,10), which has made it a public health problem (2,11). In addition, OSAHS is associated with multiple cardiovascular, metabolic and psychosocial complications that affect the quality of life (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Awareness is increasing regarding outcome measures beyond the apnea hypopnea index. Other measures, such as general quality of life, OSA-specific quality of life, measurements of sleepiness, and performance, are being considered as reportable metrics [68, 69•]. Studies attest to the efficacy of uvulopalatopharyngoplasty (UPPP) on subjective symptoms with appropriate patient selection, in some cases even where polysomnographic improvement was not apparent [70].…”
Section: Progress In Surgical Treatment Of Osamentioning
confidence: 99%